1994
DOI: 10.1126/science.7914032
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of NF-κB Signaling by Selective Ablation of an mRNA target by 2-5A Antisense Chimeras

Abstract: Activation of 2-5A-dependent ribonuclease by 5'-phosphorylated, 2',5'-linked oligoadenylates, known as 2-5A, is one pathway of interferon action. Unaided uptake into HeLa cells of 2-5A linked to an antisense oligonucleotide resulted in the selective ablation of messenger RNA for the double-stranded RNA (dsRNA)-dependent protein kinase PKR. Similarly, purified, recombinant human 2-5A-dependent ribonuclease was induced to selectively cleave PKR messenger RNA. Cells depleted of PKR activity were unresponsive to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
182
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 221 publications
(189 citation statements)
references
References 30 publications
7
182
0
Order By: Relevance
“…In addition, a long-term and productive collaboration with chemist, Paul Torrence at the National Institutes of Health continued after the move to Cleveland. These efforts were aimed at directing RNase L to cleave target RNAs in vivo [48,49]. Cloning of RNase L provided the first real insight into the enzyme and contributed to, or was complemented by, many interesting and important findings by several different labs.…”
Section: Molecular Cloning Of Rnase Lmentioning
confidence: 99%
“…In addition, a long-term and productive collaboration with chemist, Paul Torrence at the National Institutes of Health continued after the move to Cleveland. These efforts were aimed at directing RNase L to cleave target RNAs in vivo [48,49]. Cloning of RNase L provided the first real insight into the enzyme and contributed to, or was complemented by, many interesting and important findings by several different labs.…”
Section: Molecular Cloning Of Rnase Lmentioning
confidence: 99%
“…For our initial studies, therefore, we selected U251-MG cells for antisense treatment because they had the highest level of telomerase activity. Previous experience with targeting the PKR mRNA (Maran et al, 1994) and an RSV mRNA (Cirino et al, 1997) using speci®c 2-5A-linked oligonucleotides had demonstrated that the target RNA was degraded after 4 ± 5 h. We therefore treated aliquots of U251-MG cells with the`active' oligonucleotide and the two controls for 5 h. RNA was then prepared from these cells and subjected to RT ± PCR to detect telomerase RNA. GAPDH mRNA was used to demonstrate a lack of non-speci®c activity of these oligonucleotides in these cells.…”
Section: E Ect Of Antisense Telomerase In Vitromentioning
confidence: 99%
“…2-5A antisense refers to a class of oligonucleotide therapeutic agents that cause the catalytic breakdown of target RNA molecules Maran et al, 1994;Maitra et al, 1995;Cirino et al, 1997). These drugs contain a 2',5'-linked tetraadenylate (2-5A) covalently attached through linkers to antisense oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations